Management Library Based on Digital Literacy at school Berau State High School (Study Cases at State Senior High School 4 and State Senior High School 6 Berau) - Kusmiati, Tatik; Nurlaili, Nurlaili; Akhmad, Akhmad; Warman, Warman; Mulawarman, Widyamitmike Gede; Azainil, Azainil (Lentera Pustaka: Jurnal Kajian Ilmu Perpustakaan, Informasi dan Kearsipan, 2025)
Background: The transformation of traditional libraries into digital ones has become essential for the learning process. On one hand, libraries are required to provide digital resources, while on the other, students are expected to be literate in using them.Objective: This research aims to describe the planning, organizing, implementation, supervision, challenges, and impacts in managing a digital literacy-based library at SMA Negeri BerauMethods: This study employs a qualitative approach using a case study method. The research was conducted at SMA Negeri 1 and SMA Negeri 4 Berau, using observation, interviews, and documentation for data collection. The data analysis follows the interactive model of Miles and Huberman and the Pattern Matching technique by Robert K. Yin.Results: The planning of digital-based libraries in both schools begins with identifying digital resource needs. In terms of organization, both schools have a clear management structure. The implementation phase involves various strategic programs. In the evaluation phase, both schools apply a continuous monitoring and assessment system. The impact of digital libraries includes easier access, increased efficiency in information retrieval, and changes in the usage patterns of library resources. The pattern matching results conclude that the library management in both schools aligns with theoretical models.Conclusion: The four main aspects of educational management have been effectively implemented in both schools. The implications of this research reinforce the concept of digital literacy in relation to the ability to use digital resources critically.